A concept analysis of Self-management among diabetes mellitus - Satriya Pranata; Herlinda Wulandari (International Journal of Nursing and Health Services (IJNHS), 2021)
The mortality and morbidity due to Diabetes Mellitus (DM) are increasing every year. Effectively in self-management has been demonstrated to conjunction patients with a health provider and support system to solve the patient's problem. Self-management in DM is very popular but still complex and abstract. Ambiguity regarding the intention of self-management in DM can cause confusion and misunderstanding among health professionals about the purpose and the application in the clinical situation. A perceptible definition regarding self-management for diabetes is required for clinical setting implication and future research. The study aimed to clarify and formalize the concept analysis of self-management in DM. We clarify the meaning of self-management in DM with concept analysis as outlined by Walker and Avant (2005). Attributes of self-management in diabetes were glycemic control process and activities, self-control, health-seeking, problem-solving, and decision making. Antecedents, consequences, and empirical referents are explained. Model, borderline, related, and contrary cases are explaining to clear and clarify the concept. Defining the concept can help the researcher solve the patient's problem about conjunction among patients with a health provider. Health professionals can advocate for antecedents in self-management and evolve interventions to support self-management attributes to serve patients in preventing complications